The global incidence of lip, oral cavity, and pharyngeal cancers by subsite in 2012. (19th October 2016) - Shield, Kevin D.; Ferlay, Jacques; Jemal, Ahmedin; Sankaranarayanan, Rengaswamy; Chaturvedi, Anil K.; Bray, Freddie; Soerjomataram, Isabelle
ABSTRACT: By using data from the International Agency for Research on Cancer publication Cancer Incidence in 5 Continents and GLOBOCAN, this report provides the first consolidated global estimation of the subsite distribution of new cases of lip, oral cavity, and pharyngeal cancers by country, sex, and age for the year 2012. Major geographically based, sex‐based, and age‐based variations in the incidence of lip, oral cavity, and pharyngeal cancers by subsite were observed. Lip cancers were highly frequent in Australia (associated with solar radiation) and in central and eastern Europe (associated with tobacco smoking). Cancers of the oral cavity and hypopharynx were highly common in south‐central Asia, especially in India (associated with smokeless tobacco, bidi, and betel‐quid use). Rates of oropharyngeal cancers were elevated in northern America and Europe, notably in Hungary, Slovakia, Germany, and France and were associated with alcohol use, tobacco smoking, and human papillomavirus infection. Nasopharyngeal cancers were most common in northern Africa and eastern/southeast Asia, indicative of genetic susceptibility combined with Epstein‐Barr virus infection and early life carcinogenic exposures (nitrosamines and salted foods). The global incidence of lip, oral cavity, and pharyngeal cancers of 529, 500, corresponding to 3.8% of all cancer cases, is predicted to rise by 62% to 856, 000 cases by 2035 because of changes in demographics. Given the rising incidence of lip, oral cavity, and pharyngeal cancers and the variations in incidence by subsites across world regions and countries, there is a need for local, tailored approaches to prevention, screening, and treatment interventions that will optimally reduce the lip, oral cavity, and pharyngeal cancer burden in future decades.CA Cancer J Clin 2017;67:51–64. © 2016 American Cancer Society .